Remote ischemic preconditioning STAT3-dependently ameliorates pulmonary ischemia/reperfusion injury. - Nanfu Luo; Jin Liu; Yan Chen; Huan Li; Zhaoyang Hu; Geoffrey W Abbott (PLoS ONE, 2018)
The lungs are highly susceptible to injury, including ischemia/reperfusion (I/R) injury. Pulmonary I/R injury can occur when correcting conditions such as primary pulmonary hypertension, and is also relatively common after lung transplantation or other cardiothoracic surgery. Methods to reduce pulmonary I/R injury are urgently needed to improve outcomes following procedures such as lung transplantation. Remote liver ischemic preconditioning (RLIPC) is an effective cardioprotective measure, reducing damage caused by subsequent cardiac I/R injury, but little is known about its potential role in pulmonary protection. Here, we analyzed the efficacy and mechanistic basis of RLIPC in a rat model of pulmonary I/R injury. RLIPC reduced lung I/R injury, lessening structural damage, inflammatory cytokine production and apoptosis. In addition, RLIPC preserved pulmonary function compared to controls following lung I/R injury. RLIPC stimulated phosphorylation of pulmonary STAT3, a component of the SAFE signaling pathway, but not phosphorylation of RISK pathway signaling proteins. Accordingly, STAT3 inhibition using AG490 eliminated the pulmonary protection afforded by RLIPC. Our data demonstrate for the first time that RLIPC protects against pulmonary I/R injury, via a signaling pathway requiring STAT3 phosphorylation.